2021
DOI: 10.2355/isijinternational.isijint-2020-574
|View full text |Cite
|
Sign up to set email alerts
|

Iron Ore Sintering in Milli-Pot: Comparison to Pilot Scale and Identification of Maximum Resistance to Air Flow

Abstract: In the iron ore sintering process, the resistance to air flow is a major factor in deciding the flame front speed, which influences the sinter productivity and quality. In this work, pressure drop during sintering and the resistance to air flow was investigated in milli-pot sintering for different coke rates. The sintering experiments were conducted in a milli-pot (diameter 53 mm, height 400 mm) and pressure and temperature were measured at the same locations in the bed by four taps located equidistant to each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Several zones can be classified based on temperature alone which contributes to the total pressure-drop during sintering, i.e., humidified bed (HB) zone ( < ~60°C), de-humidification and goethite dehydroxylation zone (~100°C to ~620°C), calcination zone ( > ~700°C), combustion zone ( > ~727°C), melting zone ( > ~1 200°C) and sintered bed (SB) zone ( < ~1 200°C on the cooling side). [7][8][9][10][11][12][13] Some studies have specifically focused on resistance to air flow in the flame front zone, 5,10,[14][15][16][17][18][19] however, the characteristics of this zone including the bed structure that contributes to flow resistance are complex and still not well understood. Loo 7) defined the flame front as a zone with a leading-edge where the coke particles start to combust and a trailing edge where the coke particles are fully combusted and reported that the flame front is responsible for maximum pressure drop in the bed during sintering.…”
Section: Quantification Of Resistance and Pressure Drop At High Tempe...mentioning
confidence: 99%
See 4 more Smart Citations
“…Several zones can be classified based on temperature alone which contributes to the total pressure-drop during sintering, i.e., humidified bed (HB) zone ( < ~60°C), de-humidification and goethite dehydroxylation zone (~100°C to ~620°C), calcination zone ( > ~700°C), combustion zone ( > ~727°C), melting zone ( > ~1 200°C) and sintered bed (SB) zone ( < ~1 200°C on the cooling side). [7][8][9][10][11][12][13] Some studies have specifically focused on resistance to air flow in the flame front zone, 5,10,[14][15][16][17][18][19] however, the characteristics of this zone including the bed structure that contributes to flow resistance are complex and still not well understood. Loo 7) defined the flame front as a zone with a leading-edge where the coke particles start to combust and a trailing edge where the coke particles are fully combusted and reported that the flame front is responsible for maximum pressure drop in the bed during sintering.…”
Section: Quantification Of Resistance and Pressure Drop At High Tempe...mentioning
confidence: 99%
“…Loo 7) defined the flame front as a zone with a leading-edge where the coke particles start to combust and a trailing edge where the coke particles are fully combusted and reported that the flame front is responsible for maximum pressure drop in the bed during sintering. 5,7) In a previous work of the authors, 14) it was shown that the maximum pressure-drop occurs in a zone called as "region of maximum resistance" (RMR), which starts from 100°C in the leading-edge and includes Loo's flame front (coke combustion) along with other physico-chemical processes such as de-humidification, goethite dehydroxylation, flux calcination and granulate melting.…”
Section: Quantification Of Resistance and Pressure Drop At High Tempe...mentioning
confidence: 99%
See 3 more Smart Citations